Gac aril and gum xanthan supplementation in wheat macaroni pasta production - Nguyen Minh Thuy; Nguyen Thi Tieu Phung; Tran Ngoc Giau; Vo Quoc Tien; Ngo Van Tai; Vo Quang Minh (My University, 2023)
1Institute of Food and Biotechnology, Can Tho University, Vietnam 2School of Food Industry, King Mongkut’s Institute of Technology Ladkrabang, Thailand 3College of Environment and Natural Resources, Can Tho University, Vietnam
Keywords: Aril; Agronomic Practices and Intercropping Systems